Rainfall partitioning in the Cerrado and its influence on net rainfall nutrient fluxes - Tonello, Kelly Cristina; Rosa, Alexandra Guidelli; Pereira, Luara Castilho; Matus, Gregorio Nolazco; Gamero Guandique, Manuel Enrique [UNESP]; Navarrete, Acacio Aparecido (Elsevier B.V., 2021)
Quantitative studies on the water and nutrient enrichment of throughfall and stemflow in the Cerrado are lacking, especially among tree species. This work tested the hypothesis that the chemistry of rainfall fractions is altered after passing through the canopy and that the chemistry of stemflow can substantially change among tree species. We compared the nutrient concentrations in rainfall, throughfall and stemflow, dry deposition and canopy exchange among eight Cerrado species in Brazil. Rainfall, throughfall and stemflow were monitored from April 2018 to March 2019. The following chemical factors were determined using a Metrohm liquid chromatograph ECO IC: Na2+, K+, Ca2+, Mg2+, Br-, Cl-, NO3-, SO42- and PO43-. The enrichment ratio, depositions of rainfall, throughfall and stemflow and canopy budget of different nutrients were calculated for the stand and species. A comparison between the mean concentrations showed that most of the elements and compounds were relatively more concentrated in the throughfall and stemflow, except for Na(2+)and Ca2+, which were more concentrated in the rainfall (p<0.05). We noted that each species had a specific contribution to the stemflow nutrients. The different components and canopy geometry, as well as the bark morphology of the studied species, contributed varying proportions to the nutrient fluxes. The stemflow deposition of most nutrients was significantly higher in Xylopia aromatica. The highest nutrient input by stemflow was observed for K+, which ranged from 2.13 (A. peregrina) to 77.36 (X. aromatica) kg ha(-1) y(-1). A canopy budget model indicated that canopy exchange was often more dominant than dry deposition. Unlike the other nutrients, Cl and PO43- were taken up by the canopy. Given the variation in the nutrient input, these results highlight the importance of investigating the individual contribution of the stemflow of each species in the Cerrado forest and provide a potential strategy for adapting the species to soil recovery.
Keywords: Bark texture; Canopy budget model; Canopy exchange; Dry deposition; Forest hydrology; Forest meteorology